A Simplified Working Classification for Planning and Management of Facial Fractures - Mukesh K. Sharma; Rahul Saini; Bulli B. Boyidi; Vaddi S. Babu (Indian Journal of Plastic Surgery)
Facial fractures are commonly encountered by plastic and maxillofacial surgeons. Although very diversified in nature, their treatment planning requires a thorough knowledge of the facial anatomy and advanced treatment modalities. With the advent of three-dimensional computed tomography, it has become a lot easier to diagnose and treat them accordingly. It is important to categorize facial fractures for an effective liaison between the radiologists, surgeons, and medical staff involved in their management. Various classification schemes have been made to classify them, but they are cumbersome to remember and communicate among treating doctors. We present a new yet simple facial fracture classification that is based on the facial buttresses involved. This helps in better and uniform management of fracture patterns and also anticipates future complications that may arise from such fractures, if any.